Predicting neonatal RDS with fetal pulmonary artery doppler: a diagnostic performance and ROC curve analysis - Kumar, Ishan; Kukreja, Karan; Kumar, Ashok; Aggarwal, Priyanka; Sachan, Shikha; Verma, Ashish (The Ultrasound Journal, 2025)
Study design: Prospective observational diagnostic accuracy study. Methods: This study evaluated Doppler parameters of the fetal main pulmonary artery (MPA) as potential noninvasive predictors of RDS and to assess their relationship with gestational age and postnatal respiratory outcomes. Pulsed-wave Doppler of the fetal MPA was performed and Doppler indices—pulsatility index (PI), resistance index (RI), peak systolic velocity (PSV), and acceleration time/ejection time ratio (At/Et)—were recorded over three cardiac cycles and averaged. Values were compared after delivery between neonates with and without RDS. Results: In normally developing fetuses, PI and RI decreased while At/Et increased with advancing gestational age. In contrast, fetuses who developed RDS showed persistently low At/Et and elevated PI and RI values. Cutoff values of At/Et < 0.24, RI > 0.8, and PI > 2.16 were effective in predicting RDS. The severity of RDS was associated with greater deviations from these values. Altered Doppler indices were found to be independent predictors of RDS in preterm neonates. Conclusion: Fetal MPA Doppler parameters serve as reliable, non-invasive predictors of RDS and the severity of RDS in preterm neonates.